2018
DOI: 10.3389/fvets.2018.00252
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety of Intraperitoneal Radio Transmitter Implants in Brown Bears (Ursus arctos)

Abstract: Intraperitoneal radio transmitters have been widely used in free-ranging wild mammals, but there are no long-term studies on their biocompatibility or technical stability within the abdominal cavity of animals. Possible negative health effects may bias results from ecological studies on instrumented animals and raise concerns over animal welfare issues. The aim of this study was to evaluate the long-term technical stability and pathological effects of Telonics intraperitoneal very high frequency (VHF) radio tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Particularly problematic is the use of implanted transmitters as this involves additional trauma to the animal. The recent study by Arnemo et al (2018) showed that transmitters implanted into the abdominal cavities of brown bears Ursus arctos performed poorly and were not biocompatible, in several cases causing the animal's death. Several cases of mortality caused by implanted radio-transmitters have been reported also in European lynx Lynx lynx (Lechenne et al 2012), Harlequin ducks Histrionicus histrionicus (Mulcahy and Esler 1999) and American badgers Taxidea taxus (Quinn et al 2010).…”
Section: Radio-transmittersmentioning
confidence: 99%
“…Particularly problematic is the use of implanted transmitters as this involves additional trauma to the animal. The recent study by Arnemo et al (2018) showed that transmitters implanted into the abdominal cavities of brown bears Ursus arctos performed poorly and were not biocompatible, in several cases causing the animal's death. Several cases of mortality caused by implanted radio-transmitters have been reported also in European lynx Lynx lynx (Lechenne et al 2012), Harlequin ducks Histrionicus histrionicus (Mulcahy and Esler 1999) and American badgers Taxidea taxus (Quinn et al 2010).…”
Section: Radio-transmittersmentioning
confidence: 99%
“…Transmitter loss was also reported for birds and reptiles (47,48). In contrast, in a study implanting 305 brown bears with VHF transmitters reported no loss (11). These contrasting ndings indicate that species differences (physiology, immune system etc.)…”
Section: Pit Tagsmentioning
confidence: 85%
“…Most studies have reported successful results without complications, whereas others document varying tissue responses. A study on brown bears (Ursus arctos) reported corrosion of parts of implanted devices and leakage from short-circuited batteries, which resulted in the death of two study animals (11). The same study found a varying degree of tissue foreign body reaction to the implanted devices, ranging from no reaction to light encapsulation to thick capsule formation.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The lack of expertise can unfortunately result in failing to ask the important questions to the investigators. Examples of such questions include asking how a transmitter is aerodynamically designed, rather than just asking how much the transmitter weighs in relation to the weight of the animal, or how the transmitter can affect movement and health of the animals ( 15 , 29 ), or the short- and long-term risks on health and welfare from capture and handling ( 4 ). The research procedures in traditional laboratory settings affect animals confined in a controlled environment.…”
Section: The Gray Area Between Using Wild Animals For Research or Formentioning
confidence: 99%